Language, gender and leadership communication in the apprentice Asia - Evangelista, Jessica Lace G. (2014)
Language and gender are two widely researched topics in sociolinguistics. However, only a few studies dealing with the relationship of the two in natural workplace communication and in media can be found. Leadership is a gendered concept and most literature associate it with the male gender as the standard norm. This study looks at some of the strategies implemented by one male and one female finalist in the first airing of The Apprentice Asia television show on practicing leadership. The study explores the way both finalists open their meetings, give instructions, manage their meetings, and evaluate the performance of their co-workers. The results of this research study show that leaders make use of various styles of leadership that range from feminine or relational to masculine and transactional. More positively regarded leaders, however, are able to combine these strategies more adeptly in one conversation.​
Keywords: Language and gender